Javanese Perspective of Nonverbal Language: An Ethnopragmatic Study - pranowo, Pranowo (Bina Nusantara University, 2019)
The research focused on nonverbal language (NvL) of Javanese people in Indonesia who spoke the first Javanese language and the second language Indonesian using an ethnopragmatic approach. The purpose of research was to describe the perception of the Javanese community on the use of NvL, both dynamic and static NvL. This research used a descriptive qualitative method with data collection techniques through observation of people who were communicating, interviews with resource persons, and recording as supporting techniques for data collection. Data were analyzed by steps; data identification, classification, and interpretation. The results of research have theoretical implications. If aspects of local wisdom such as those possessed by the Javanese people are preserved, it will be able to provide benefits to the preservation of culture that has been passed down through generations in Javanese society. Such conditions will be able to illustrate that the community’s perspective on Javanese culture is still well maintained from the past until now.